Chatbot Menggunakan Metode Levenshtein Distance Dalam Pencarian Mobil Bekas - Arsianto, Muhammad Alif Rahmat Novian; Rahani, Faisal Fajri (Jurnal Ilmu Komputer; Vol 16 No 2 (2023): Jurnal Ilmu Komputer, 2023)
Car as private transportation has an important role as a means to carry out daily activities including going to work, shopping, and other activities. The potential buyer of its vehicle often faces some difficulties related to the price and condition of the car. They were confused about finding information for the required car. Nowadays, technology is used to solve these problems. One of the methods is by using a chatbot application that applies artificial intelligence. Chatbot is a software application that replaces a live human agent to conduct a conversation via text or text to speech. Population in this research are 235 data of used car in 2020. The variables that used are brand, built year, petroleum, transmission, milestone, engine capacity, and price. The natural language programming using levenshtein distance algorithm that can be measured of difference between two strings. The stages including data preparation, cleaning, selection, transformation, grouping questions, implementation of levenshtein distance algorithm, and system testing. The aim to determine whether Chatbot using Levensthein distance algorithm is good enough to help potential buyer of used car. The accuracy value of this method reaches 69% with a total of 40 grouping questions from 2050 data.